KENDALA DAN PERBAIKAN PENDIDIKAN ISLAM YANG IDEAL - Deri Wanto (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Every era certainly has a separate challenge. In the development of the Indonesian nation from the old order to the new order era and era to the reform era that seemed to give a very clear feel and color for this nation, especially in the field of education. What has happened? Precisely education in Indonesia to get a new problem, namely the birth of